NanoBiotechnology Protocols - Rosenthal, Sandra J.; Rosenthal, Sandra J.; Wright, David W.; Wright, David W. (Methods in Molecular Biology, 2013)
Nanobiotechnology holds the promise of providing revolutionary insight into aspects biology ranging from fundamental questions such as elucidating molecular mechanisms of brain disorders to extraordinary applications such as the detection of a single cancer cell in a population of a million cells.  The second edition of Nanobiotechnology Protocols expands upon the previous editions with current, detailed protocols for nanobiotechnology; imaging and detection. With new chapters that explore nano-bio constructs and toxicology of nanomaterials. Written in the highly successful Methods in Molecular Biology™ series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Authoritative and practical, Nanobiotechnology Protocol, Second Edition highlights important current areas of development and directions of the field for the future.